Banking Crises and Market Timing: Evidence from M&As in the Banking Sector - Shen, Chung-Hua; Chen, Yehning; Hsu, Hsing-Hua; Lin, Chih-Yung (My University, 2020)
We investigate whether the gains are greater for banks that conduct mergers and acquisitions (M&As) during banking crises than during non-crisis periods. We contribute to the literature by examining 1984 M&As using global banking sample from 106 countries (areas) during 1994 ~ 2009. We find the synergistic gains of acquiring banks during banking crises are larger than those during non-crisis periods. We further find that such gains are greater when acquiring weak targets, for acquirers in developed countries, and for acquirers in domestic M&As. This study confirms that a banking crisis is an appropriate time for banks to conduct M&As.
Keywords: Banking crises; Mergers and acquisitions; Synergistic gains